Pseudotrichonotus belos new species, first record of the fish family Pseudotrichonotidae from Australia (Teleostei: Aulopiformes) - Gill, Anthony C.; Pogonoski, John J. (Zootaxa, 2016)
Pseudotrichonotus belos new species, described from three specimens trawled in 100–120 m offshore between Exmouth Gulf and Shark Bay, Western Australia, represents the first record of the sand-diving fish family Pseudotrichonotidae from Australian waters. It differs from its two congeners in having a more posteriorly positioned dorsal fin (predorsal length 39.6–41.2 % SL) and fewer dorsal- and anal-fin rays (31–33 and 12, respectively).